A REVIEW ON SOLID DISPERSION TO ENHANCE TECHNIQUE FOR POORLY WATER-SOLUBLE DRUGS AND ITS POLYMERS - Basant, Neelu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
During the formulation development process, one of the most demanding factors is still the solubility behavior of pharmaceuticals. These days, there is a sharp rise in the quantity of novel chemical entities with intermittent problems with low permeability and solubility. For medications with low water solubility, solid dispersion has been shown to be a better dosing form. The use of solid dispersions in water-soluble carriers to increase the rate of drug dissolution and bioavailability for hydrophobic medications has attracted a lot of attention. Because of solubility issues, formulation scientists continue to face challenges in improving the oral bioavailability of medications administered in solid dosage forms. The rate-limiting mechanism in the drug absorption process from a solid dosage form of relatively insoluble medicines may be the dissolving rate. Thus, one of the challenges facing formulation scientists is the rise in the solubility of poorly soluble pharmaceuticals by the use of solid dispersion techniques. Solid dispersion techniques, which reduce drug particle size, improve wettability, and produce amorphous particles, have received significant interest in enhancing the dissolving rate of highly lipophilic medicines and, consequently, improving their bioavailability. The several synthetic, natural, semisynthetic, and modified natural hydrophilic carriers that are utilized to formulate solid dispersions are summarized in this article. We will talk about in this essay. A review of solid dispersion as an improved approach for medicines and their polymers that are poorly soluble in water.